Meninjau Ulang Penerapan Fractional Reserve Banking pada Perbankan Syariah - Ayif Fathurrahman (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2018)
This article aims to discuss fractional reserve banking applied by Islamic banking. The practice of fractional reserve banking applied by Sharia banking is part of contemporary practice that was not discovered at the time of the Prophet. Thus, a comprehensive ijtihadi study of the Islamic banking system is needed, considering that the practice of fractional reserve banking applied by Islamic banking is also part of conventional banking practices. The practice of fractional reserve banking in conventional banking has been proven to have an impact on banking institutions and has an impact on the monetary crisis which destabilizes the country's economic stability. In addition, the practice of fractional reserve banking also contradicts Islamic law, for example Meera and Moussa (2009) stated in their research that fractional reserve banking was not in accordance with Islamic principles, because it contradicted the concept of al-milkiyah (ownership) in Islam. This can be seen from the creation of money through fractional reserve banking with the creation of purchasing power of nothingness (creating money out of nothing) which will have an impact on the unfairness of transfer of asset ownership in the structure of the economy, because transfer of ownership is not based on human effort by taking it legally and not with the knowledge or approval of the initial fund owner. This violates the principles of ownership in Islam and is tantamount to theft, let alone this system is very closely related to elements of usury. Publicity according to Sani and Aziuddin (2013) also concluded that fractional reserve banking is not allowed in the Islamic perspective. This perspective is based on the maqasid syariah parameters used to measure empirically the implications of the frational reserve banking system on the economic stability of the community.